Implementation of Textual Concrete Syntax - Lämmel, Ralf (Software Languages, 2018)
This chapter discusses implementation aspects of textual concrete syntax: parsing, abstraction, formatting, and the use of concrete as opposed to abstract object syntax in metaprograms. We focus on how parsers, formatters, etc. are actually implemented in practice, subject to using appropriate libraries, tools, and metaprogramming techniques.